Paradoksy królestwa Bożego (Mdr 3,1-9 i 5,15-16) - Poniży, Bogdan (Poznańskie Studia Teologiczne, 2009)
The Book of Wisdom, which was written on the eve of the New Testament, enriches significantly the Old Testament teaching about God’s payment. In the very heart of the eschatological part (chapters 3-4) it presents three situations, which at first glance seem to question God’s justice (the suffering of the just one, lack of offspring, premature death). The analized text (1-9,5, 15-16) is the most important expression of the awareness of afterlife gained by the Israel in the late period of the Old Testament and the most powerful evidence of that belief.